BDPQ integrated: contemporary jewellery inspired by tangram - Jalaludin, Mohd Faiz; Mohd Sharif, Mohd Hakim; Muda, Muhammad Shafiq; Mohd Hasan, Adib (Universiti Teknologi MARA, Kedah, 2023)
This research paper explores the concept of "BDPQ Integrated: Contemporary Jewellery Inspired by Tangram." The objective of this study is to examine the intersection of tangram puzzles and contemporary jewellery design, investigating how tangram serves as a source of inspiration forcreating unique and aesthetically appealing jewellery pieces. The paper begins with an introduction to tangram's historical significance and its components, emphasizing its cultural relevance. It then delves into contemporary jewellery design, highlighting trends and influences shaping the field. The problem statement focuses on the lack of comprehensive exploration of tangram's impact on jewellery design, particularly in the contemporary context. To address this, the research methodology involves analyzing case studies of jewellery pieces inspired by tangram, examining their design techniques, materials, and concepts. The findings reveal the creative ways in which tangram elements, symbolism,and aesthetics are incorporated into contemporary jewellery, resulting in visually captivating and thought-provoking pieces. The commercialization potential of tangram-inspired jewellery is alsodiscussed, exploring the reception among consumers and collectors. The conclusion summarizes the research, emphasizing the unique blend of tradition and innovation in tangram-inspired jewellery, and highlighting the cultural and artistic significance of this creative fusion. Overall, this study contributesto the understanding of the relationship between tangram and contemporary jewellery design, providing insights into the design process, findings, and commercial possibilities, while showcasing the enduring appeal of tangram as a source of inspiration in the jewellery industry.